2023
DOI: 10.3390/ijms241210233
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 Based on Nucleic Acid Amplification Tests (NAATs) and Its Integration into Nanomedicine and Microfluidic Devices as Point-of-Care Testing (POCT)

Abstract: The coronavirus SARS-CoV-2 has highlighted the criticality of an accurate and rapid diagnosis in order to contain the spread of the virus. Knowledge of the viral structure and its genome is essential for diagnosis development. The virus is still quickly evolving and the global scenario could easily change. Thus, a greater range of diagnostic options is essential to face this threat to public health. In response to the global demand, there has been a rapid advancement in the understanding of current diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Integrating RPA with microfluidic devices has the potential to facilitate the use of nucleic acid detection assays at the POC with great simplicity and easy operation [59]. MiCaR, a nucleic acid testing platform, was proposed to detect nine HPV subtypes.…”
Section: Fluorescence-based Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating RPA with microfluidic devices has the potential to facilitate the use of nucleic acid detection assays at the POC with great simplicity and easy operation [59]. MiCaR, a nucleic acid testing platform, was proposed to detect nine HPV subtypes.…”
Section: Fluorescence-based Detection Methodsmentioning
confidence: 99%
“…Figure 4 illustrates the strategy for using centrifugal microfluidic devices to detect multiple SARS-CoV-2 genes. Another advantage of RPA is that it can be combined with other isothermal techniques, such as LAMP, to increase sensitivity and decrease false-positive signals [59,63]. A novel one-pot solid-phase RPA coupled with a CRISPR-based system was developed for multiplex detection of SARS-CoV-2 genes [64].…”
Section: Fluorescence-based Detection Methodsmentioning
confidence: 99%
“…The level of the test line signal is directly proportional to the concentration, and it is even possible to obtain a quantitative value using an electronic sensor device [6] . Many studies reported the use of nucleic acids instead of proteins in lateral flow assays [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] . However, there was no significant progress or widespread application on the commercial side.…”
Section: Introductionmentioning
confidence: 99%
“…However, along with the intrinsic characteristics of viral RNA polymerases, the viral genome can undergo recombination and reassortment, contributing to high diversity and the emergence of new variants. Thus, the availability of assays for diagnosing/monitoring the infectious agent remains an essential component of infection control strategies [12].…”
Section: Introductionmentioning
confidence: 99%
“…While isolation and identification of the infectious agent are considered standards for clinical laboratory diagnosis, it is essential to acknowledge that these techniques are labor-intensive, time-consuming, and possess limited sensitivity [30]. Conversely, nucleic acid amplification tests (NAATs) have demonstrated remarkable specificity and sensitivity in detecting the etiological agents of infections, surpassing conventional culture-based testing methods [12,31]. Multiplex polymerase chain reaction (PCR)-based tests, for instance, enable the simultaneous detection of several molecular markers using distinct pairs of oligonucleotide primers.…”
Section: Introductionmentioning
confidence: 99%